Observations on the agonistic behaviour of Lepadogaster lepadogaster purpurea (Pisces: Gobiesocidae) - Gonçalves, Emanuel João (2012)
Agonistic behaviour of captive Lepadogaster lepadogaster purpurea was described, forming the first record of such behaviour in the family Gobiesocidae. Both male and female engaged in similar behaviours. The agonistic interactions were related mainly to the control of shelter sites and larger fish tended to chase away and take over the shelter of smaller fish.